2008
DOI: 10.1038/mi.2008.6
|View full text |Cite
|
Sign up to set email alerts
|

Protective attenuated lentivirus immunization induces SIV-specific T cells in the genital tract of rhesus monkeys

Abstract: Live attenuated lentivirus immunization is the only vaccine strategy that elicits consistent protection against intravaginal challenge with pathogenic simian immunodeficiency virus (SIV). To determine the mechanism of protection in rhesus monkeys infected with attenuated simian-human immunodeficiency virus (SHIV)89.6, a detailed analysis of SIV Gag-specific T-cell responses in several tissues including the genital tract was performed. Six months after SHIV infection, antiviral T-cell responses were rare in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 34 publications
2
75
0
Order By: Relevance
“…This concerted recall response of local and recruited memory T cells was evident in vaginal tissues in our study, in which the enhanced protection of ATRA-treated mice was revealed to be due partly to more resident memory CD8 ϩ T cells responding in situ and partly to memory cells recruited from lymph nodes. The importance of a rapid and strong CD8 ϩ T cell response at mucosal portals of viral entry in combating the establishment of systemic and chronic virus infections has been emphasized for HIV vaccines (3,14,33,50,55), and our data suggest that ATRA should be further investigated for potential incorporation into the next generation of T cell-based HIV vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…This concerted recall response of local and recruited memory T cells was evident in vaginal tissues in our study, in which the enhanced protection of ATRA-treated mice was revealed to be due partly to more resident memory CD8 ϩ T cells responding in situ and partly to memory cells recruited from lymph nodes. The importance of a rapid and strong CD8 ϩ T cell response at mucosal portals of viral entry in combating the establishment of systemic and chronic virus infections has been emphasized for HIV vaccines (3,14,33,50,55), and our data suggest that ATRA should be further investigated for potential incorporation into the next generation of T cell-based HIV vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Cell suspensions were prepared using a modification of our procedure to isolate mononuclear cells from the vagina (9,12). Freshly isolated foreskins were collected into complete RPMI 1640 medium, containing 10% fetal calf serum, 2 mM L-glutamine, 100 U ml Ϫ1 penicillin, and 0.1 mg ml Ϫ1 streptomycin (Sigma, St. Louis, MO).…”
Section: Animalsmentioning
confidence: 99%
“…An effective mucosal immune response elicited by live-attenuated SIV vaccination may prevent the initial CD4 ϩ T-cell depletion from the gut. Several recent studies confirm a critical protective role for CD8 ϩ T cells in the genital tract after vaccination with SHIV89.6, demonstrating that a mucosal immune response is capable of protecting against or ameliorating SIV infection (14)(15)(16)48). Another study has also demonstrated the presence of high-frequency, polyfunctional T-cell responses in the mucosal tissues of elite controllers, i.e., individuals who maintain plasma viral loads below 75 copies/ ml, compared to blood from the same individual, tissues of noncontrollers, and antiretroviral drug-treated patients.…”
mentioning
confidence: 99%